1996
DOI: 10.1074/jbc.271.42.25950
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic Acid Suppresses Neural Differentiation-dependent Expression of the Neurofilament-L Gene in P19 Embryonal Carcinoma Cells by Post-transcriptional Modification

Abstract: Mouse P19 embryonal carcinoma cells in aggregation culture in the presence of 10(-6) M retinoic acid followed by monolayer culture differentiate into nerve and glial cells. In this study, we demonstrated that the neurofilament-L (NF-L) mRNA and protein levels of these cells were enhanced in accordance with their retinoic acid-induced neural differentiation. Okadaic acid (OA) treatment of the cells markedly suppressed this differentiation-dependent NF-L gene expression increase and neurite outgrowth of the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
(41 reference statements)
2
12
0
Order By: Relevance
“…The three LIPP and LIPG domains were readily apparent, including the N-terminal ‘lipase’ domain with the active site triad residues buried under the ‘lid’ domain observed for horse LIPP. The ‘lid’ has been previously shown to contribute to the preference for triglyceride and phopholipid substrates of other vascular lipases (LIPC and LIPL) (Dugi et al, 1995; Kobayashi et al, 1996) and may play a major role in determining the preference for phospholipid substrates for LIPG. A ‘hinge’ region was also observed for these vertebrate LIPG proteins, separating the ‘lipase’ and ‘plat’ domains, with the latter having a ‘sandwich-like’ β-pleated sheet structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three LIPP and LIPG domains were readily apparent, including the N-terminal ‘lipase’ domain with the active site triad residues buried under the ‘lid’ domain observed for horse LIPP. The ‘lid’ has been previously shown to contribute to the preference for triglyceride and phopholipid substrates of other vascular lipases (LIPC and LIPL) (Dugi et al, 1995; Kobayashi et al, 1996) and may play a major role in determining the preference for phospholipid substrates for LIPG. A ‘hinge’ region was also observed for these vertebrate LIPG proteins, separating the ‘lipase’ and ‘plat’ domains, with the latter having a ‘sandwich-like’ β-pleated sheet structure.…”
Section: Resultsmentioning
confidence: 99%
“…Predicted secondary structures and tertiary structures for vertebrate LIPG proteins showed a strong similarity with human and horse LIPP (Winkler et al, 1990; Bourne et al, 1994). Three major structural domains were apparent for vertebrate LIPG, including the ‘lipase’ domain containing the catalytic triad residues; the ‘lid’ which covers the active site and may contribute to the substrate specificities of neutral lipases (Dugi et al, 1995; Kobayashi et al, 1996); and the ‘plat’ domain which contributes to lipoprotein binding (Wong et al, 1991). Phylogenetic studies using 16 distinct human and mouse lipase sequences indicated that the LIPG gene has appeared early in vertebrate evolution, prior to the appearance of bony fish more that 500 million years ago.…”
Section: Resultsmentioning
confidence: 99%
“…The three LPL and LIPP domains were readily apparent, including the N-terminal `lipase' domain with the active site triad residues buried under the `lid' domain observed for horse LIPP. The `lid' has been previously shown to contribute to the preference for triglyceride and phospholipid substrates of other vascular lipases (HL and EL) (Dugi et al, 1995; Kobayashi et al, 1996) and may play a major role in determining the preference for triglyceride rich lipoprotein LPL substrates. A `hinge' region was also observed for vertebrate LPL proteins, separating the `lipase' and `plat' domains, with the latter having a `sandwich-like' β-pleated sheet structure.…”
Section: Resultsmentioning
confidence: 99%
“…Site-directed mutagenesis studies of site 3 (human HL 78Asn) have demonstrated that this N-glycosylation site is required for the efficient secretion of this liver enzyme. 64,65 …”
Section: Resultsmentioning
confidence: 99%
“…Predicted secondary structures and tertiary structures for vertebrate HL proteins showed a strong similarity with human and horse pancreatic lipases (LIPP). 29,30 Three major structural domains were apparent for vertebrate HL, including the “lipase” domain containing the catalytic triad residues; the “lid”, which covers the active site and may contribute to the substrate specificities of neutral lipases; 31,64 and the “plat” domain, which contributes to lipoprotein binding. 65 Phylogenetic studies using amino acid sequences for 13 vertebrate HL lipases, human and mouse LPL and EL, and an invertebrate lipase indicated that the LIPC gene has appeared early in vertebrate evolution, probably prior to the appearance of bony fish more that 500 million years ago.…”
Section: Resultsmentioning
confidence: 99%